IoT Modular Gateway Development for Multi-Standard Compatibility - Kattiya Kaiyarach; Sopita Taprik; Bantita Buathong; Peeramed Chodkaveekityada (My University, 2025)
Currently, IoT wireless communication technology plays a crucial role in connecting multiple devices. However, the diverse standards used limit their interoperability. To address the issue of incompatible communication protocols, this research presents a developed IoT system that seamlessly integrates various communication standards. The system comprises a central processing unit (Core Board) that functions as an IoT gateway. This core board connects local networks via LoRa and others, as well as public networks using 3G and Wi-Fi. The system utilizes the STM32H563ZI processor, which is based on the ARM Cortex M33 architecture. Additionally, it features expansion slots to accommodate future of others communication standards. The results show that the developed IoT system's effective support for a diverse range communication standards.
Keywords: Robotics and Automated Systems